Differences in perioperative femoral and radial arterial blood pressure in neonates and infants undergoing cardiac surgery requiring cardiopulmonary bypass - Hwa Jin Cho; Sang Hoon Lee; In Seok Jeong; Nam Sik Yoon; Jae Sook Ma; Byoung Hee Ahn (Brazilian Society of Pediatrics, 2018)
Objective: Several reports claim that blood pressure (BP) in the radial artery may underestimate the accurate BP in critically ill patients. Here, the authors evaluated differences in mean blood pressure (MBP) between the radial and femoral artery during pediatric cardiac surgery to determine the effectiveness of femoral arterial BP monitoring. Method: The medical records of children under 1 year of age who underwent open‐heart surgery between 2007 and 2013 were retrospectively reviewed. Radial and femoral BP were measured simultaneously, and the differences between these values were analyzed at various times: after catheter insertion, after the initiation of cardiopulmonary bypass (CPB‐on), after aortic cross clamping (ACC), after the release of ACC, after weaning from CPB, at arrival in the intensive care unit (ICU), and every 6 h during the first day in the ICU. Results: A total of 121 patients who underwent open‐heart surgery met the inclusion criteria. During the intraoperative period, from the beginning to the end of CPB, radial MBPs were significantly lower than femoral MBPs at each time‐point measured (p < 0.05). Multivariate analysis showed that longer CPB time (>60 min, odds ratio: 7.47) was a risk factor for lower radial pressure. However, discrepancies between these two values disappeared after arrival in the ICU. There was no incidence of ischemic complications associated with the catheterization of both arteries. Conclusion: The authors suggest that femoral arterial pressure monitoring can be safely performed, even in neonates, and provides more accurate BP values during CPB‐on periods, and immediately after weaning from CPB, especially when CPB time was greater than 60 min.